The Legal Status of AYDA in Bankruptcy: Conflicts of Legal Norms and Implications for the Bankruptcy Estate - Chandra Nadhi; M. Hadi Shubhan; Faizal Kurniawan; Qomara Sari; Astrid Athina Indradewi (Greenation International Journal of Law and Social Sciences, 2026)
This study examines the legal position of collateral in the form of debtor-owned land that has been taken over by a bank through Agunan yang Diambil Alih (AYDA) in bankruptcy proceedings, particularly to determine whether such collateral remains part of the bankruptcy estate after the debtor is declared bankrupt. This research employs a normative legal method using statutory and conceptual approaches. It analyzes regulations related to bankruptcy law and AYDA, including the Banking Law, the Bankruptcy and Suspension of Debt Payment Obligations (PKPU) Law, Financial Services Authority (OJK) regulations, and relevant Supreme Court Circular Letters. The study finds that collateral under AYDA that has been legally transferred to the bank is no longer part of the bankruptcy estate. Conversely, collateral that has not been legally transferred through AYDA remains included in the bankruptcy estate. This study provides legal clarity for banks, curators, and other stakeholders regarding the status of AYDA collateral in bankruptcy proceedings, thereby supporting greater legal certainty and minimizing disputes in practice. This research offers a focused legal analysis on the intersection between AYDA mechanisms and bankruptcy law, an area that remains relatively underexplored, particularly in relation to determining the status of transferred collateral within the bankruptcy estate.